Expert multistakeholder engagement informing content of advanced diploma in visual impairment studies - Maesala Manis; Maximus M. Sefotho; Ronél Ferreira (African Vision and Eye Health, 2024)
Background: This study evaluates the interface between expert multistakeholder engagement and the development of Advanced Diploma in Visual Impairment Studies (VIS). Additionally, the study validates the content included in the modules of this training programme for teachers of learners with visual impairment (VI).